KAJIAN LITERATUR: ANALISIS PERAN PELATIHAN KESELAMATAN KERJA BAGI GURU DALAM MANAJEMEN LABORATORIUM IPA - Nugraheni, Saniyatun; Raida, Sulasfiana Alfi (EDUBIOLOCK, 2025)
Safety training in laboratories is very important for teachers so that science learning can be carried out safely and effectively. This research is a literature review using the SLR (Systematic Literature Review) method. The study began by identifying various articles discussing laboratory management, with a focus on workplace safety training in laboratories. The articles obtained through the identification process were then selected, resulting in 15 relevant articles for the study. Effective training has been proven to enhance in-depth knowledge of safety protocols, practical skills in identifying and addressing potential hazards, and instilling awareness of the importance of a safety culture. However, the implementation of workplace safety training for science teachers faces various challenges, such as time and resource constraints, lack of administrative support, and the need for relevant and engaging training materials.